Dodecanuclear [MnIII6LnIII6] species: synthesis, structures and characterization of magnetic relaxation phenomena1. Issue 26 (14th July 2015) - Tziotzi, Thomais G.; Tzimopoulos, Demetrios I.; Lis, Tadeusz; Inglis, Ross; Milios, Constantinos J.
<x xml:space="preserve">Abstract</x> Two dodecametallic heteronuclear manganese–lanthanide [MnIII6LnIII6] (Ln = Gd, Dy) complexes were isolated and characterized by magnetic measurements.